Cadeia de suprimentos: avaliação para seleção de fornecedores verdes em um hospital universitário - Santos, Bruno Miranda dos (2018)
Due to increased consumer awareness and government pressures on environmental issues, organizations are emphasizing the importance of sustainability in supply chain operations through the selection of green suppliers. This can be done through the adoption of Green Supply Chain Management (GSCM) practices. In view of this context, the objective of this study is to propose a systematic evaluation to selection of green suppliers for multicriteria decision making in a University Hospital located in the central region of the state of Rio Grande do Sul. This study proposes a framework for evaluating green suppliers through the Shannon Entropy Method and selecting the supplier with the best overall performance through the Method to evaluate the performance of alternatives through similarity with the ideal solution, better known as TOPSIS, in conjunction with the Fuzzy Set Theory to deal with imprecision and uncertainty of responses. A Sensitivity Analysis was used at the end to test the robustness of the proposal. A sustainable contracting case for Retractable Safety Syringes (SRS) is presented as an illustration of the proposed framework. For this, seven environmental criteria were defined, based on the state of the art of sustainable operations management to evaluate three potential suppliers and select the alternative with better environmental performance. As for the data collection, three specialists in the area of supply chain management and procurement were interviewed in order to assign their classifications to criteria and suppliers. According to the findings of Shannon's Entropy, the ranking of the first criteria that should predominantly be taken into account in a context of sustainable contracting for this type of product are the Product packaging, Management commitment with the GSCM and Logistics practices reverse. The ranking of the suppliers obtained through the Fuzzy TOPSIS Method indicates that the A₂ supplier presented the best overall performance against the alternatives. Finally, twenty experiments of alternating the weights of the criteria were performed in the Sensitivity Analysis to test the stability of the decision making. The ranking of the alternatives remained the same as that obtained by the Fuzzy TOPSIS Method, indicating consistency in decision making.